Approach to management of hypo and hyperthyroidism in Bangladesh: a nationwide physicians’ perspective survey - Selim, Shahjada; Mustari, Marufa; Khan, Tawshique Ahmed; Kamrul-Hasan, ABM (Frontiers in Endocrinology, 2024)
Introduction: Thyroid disorders are common clinical conditions globally. The objective of the present study was to evaluate the physicians' approach to the diagnosis and treatment of thyroid disorders in Bangladesh.The present nationally representative cross-sectional study was conducted among 662 physicians of different levels (general practitioners as well as specialists) from different hospitals in Bangladesh from January to June 2023. A self-administered semi-structured questionnaire including information about demographics and practice patterns for the diagnosis and management of thyroid disorders was used for data collection. Descriptive statistics were used to analyze the data.The American Thyroid Association (ATA) guidelines were the most commonly followed guidelines for the diagnosis and management of thyroid disorders (60%), followed by the American Association of Clinical Endocrinologists (AACE) guidelines (18%) and the European Thyroid Association (ETA) guidelines (9%). Serum TSH, free T3 and free T4 levels were the most frequently used diagnostic tests for the evaluation and follow-ups of both hypothyroid and hyperthyroid states in adults, pregnant women and children, followed by total T3 and total T4 levels. Other tests, such as anti-TPO antibody, anti-TG antibody, anti-TPO, ultrasound scan of the thyroid gland, etc., were rarely used by the participating physicians.Levothyroxine at a dose of 25 to 50 mcg and carbimazole at a dose of 30 to 45 mg were the most frequently used drugs for hypothyroid and hyperthyroid patients, respectively. Almost 65% of the physicians suggested routine thyroid function tests before surgery. In addition, more than 90% of the physicians agreed that thyroid screening for pregnancy, neonates, school children and adults would be mandatory.The majority of the physicians participating in our study followed relevant guidelines for the diagnosis and management of thyroid disorders in Bangladesh. However, there are still some gaps to be improved, as a good number of physicians did not follow specific guidelines for these disorders.